Improving Data Science Literacy Through Training at the Auxano Indonesia Muda Foundation: Peningkatan Literasi Sains Data Melalui Pelatihan Di Yayasan Auxano Indonesia Muda - Bakti Siregar; Monica Mayeni Manurung; Chello Frhino Mike Mandolang; Olivia Meilinda Davtin Pesireron (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Data science literacy refers to an individual’s ability to understand, process, and utilize data effectively to support informed decision-making. In today’s digital era, where information is abundant, this competency has become essential across various segments of society. Responding to this need, a training program was designed and implemented to enhance the data literacy of members of the Auxano Indonesia Muda Foundation (YAIM). The program was conducted online in November 2024 by a team from the Data Science Study Program at the Institut Teknologi Sains Bandung (ITSB). The training adopted a participatory approach, incorporating conceptual materials, guided discussions, and hands-on data processing exercises. The evaluation results showed an improvement in participants’ understanding of basic data science principles and encouraged the application of data-driven approaches within their organizational activities. This initiative is expected to serve as a foundation for fostering a more analytical and structured working culture in social institutions.